2018
DOI: 10.1111/cas.13605
|View full text |Cite
|
Sign up to set email alerts
|

Hypocrellin B‐loaded, folate‐conjugated polymeric micelle for intraperitoneal targeting of ovarian cancer in vitro and in vivo

Abstract: Photodynamic therapy (PDT) is considered an innovative and attractive modality to treat ovarian cancer. In the present study, a biodegradable polymer poly (ethylene glycol) (PEG)‐poly (lactic acid)(PLA)‐folate (FA‐PEG‐PLA) was prepared in order to synthesize an active‐targeting, water‐soluble and pharmacomodulated photosensitizer nanocarrier. Drug‐loading content, encapsulation efficiency, in vitro and in vivo release were characterized, in which hypocrellin B (HB)/FA‐PEG‐PLA micelles had a high encapsulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 22 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…Target tumor cells are a straightforward targeting strategy that accelerate the phagocytosis/endocytosis of nanocarriers ( Hanahan and Weinberg, 2011 ; Liu L. et al, 2016 ; Liu et al, 2017 ). The representative receptors are CD44 receptor ( Jiang et al, 2017 ), folate (FA) receptor ( Li et al, 2018d ), transferrin receptor ( Kaspler et al, 2016 ), epidermal growth factor (EGF) receptor ( del Carmen et al, 2005 ), etc.…”
Section: Smart Polymeric Delivery System For Antitumor Photodynamic Therapymentioning
confidence: 99%
“…Target tumor cells are a straightforward targeting strategy that accelerate the phagocytosis/endocytosis of nanocarriers ( Hanahan and Weinberg, 2011 ; Liu L. et al, 2016 ; Liu et al, 2017 ). The representative receptors are CD44 receptor ( Jiang et al, 2017 ), folate (FA) receptor ( Li et al, 2018d ), transferrin receptor ( Kaspler et al, 2016 ), epidermal growth factor (EGF) receptor ( del Carmen et al, 2005 ), etc.…”
Section: Smart Polymeric Delivery System For Antitumor Photodynamic Therapymentioning
confidence: 99%
“…Such a drug delivery system significantly increases biocompatibility, extends blood circulation of HB, and shows a good targeting antitumor activity for ovarian cancer. 53 Moreover, existing paclitaxel-encapsulated hyaluronic acid ceramide nanoparticles contain HB to achieve a combined treatment of chemotherapy and PDT. 54 Lanthanide up-conversion nanoparticles (UCNP) can absorb NIR light for UV and visible emission due to their unique step-like energy level structures (Figure 11).…”
Section: F I G U R E 1 1 Schematic Of Up-conversion Nanoparticles Ucnmentioning
confidence: 99%
“…PIC with PS HUVEC and lung carcinoma, in vitro [46,47] poly(ethylene oxide)-block-poly(α,β-aspartic acid)/poly([5-aminopentyl]-α,β-aspartamide) -lung carcinoma, in vitro [48] poly(ethylene oxide)-block-poly(α,β-aspartic acid) PIC with PS lung carcinoma, in vitro [49] poly(N-methyl-2-vinylpyridinium iodide)-block-poly(ethylene oxide) PIC with PS - [50,51] [64] poly(oligo(ethylene oxide)methyl ether methacrylate)-block-poly(ʟ-lysine) O 2 production image-guided (FI), liver and breast cancer, in vitro [65] methoxy-poly(ethylene oxide)-block-poly(ε-caprolactone)-benzyl degradation macrophages and endothelial cells, in vitro [40] poly(ethylene oxide)-block-poly(ε-caprolactone) degradation colon cancer and carcinoma, in vitro [37,66,67] poly(ethylene glycol)-block-poly(lactic acid) degradation [38] poly(ethylene glycol)-block-poly(ᴅ,ʟ-lactide-co-benzyl glycidyl ether) degradation macrophage and kidney cells, in vitro [45] poly(ethylene glycol)-block-poly(ε-caprolactone)-block- aliphatic polyesters, based for instance on ε-caprolactone or lactic acid [36][37][38][39][40][41]. In particular, the degradation of polyesters in vivo, a combination of both hydrolytic and enzymatic processes, makes them a first choice for the controlled delivery of drugs [42].…”
Section: Physical Solubilization Of the Photosensitizermentioning
confidence: 99%
“…Folate (FA) has been extensively studied as a targeting moiety [116] due to the overexpression of folate receptors in a number of tumor types including ovarian [117] or breast cancers [118]. One of the most recent examples of FA use in PDT applications is by Li et al, where the authors have designed a FA-PEO-PLA construct to deliver hypocrellin B, a sensitizer extracted from fungi, to intraperitoneal tumors [39]. It was shown that the sensitizer concentration reached a maximum after 2 h in the targeted organs, as opposed to after at least 6-12 hours in other peritoneal organs, thereby creating a large window of opportunity for treatment with reduced side effects.…”
Section: The Hydrophilic Blocksmentioning
confidence: 99%